LAS CARENCIAS DE LA DEMOCRACIA ACTUAL Y LAS LIMITACIONES DE LAS TEORÍAS DE LA TRANSICIÓN (2010)
ABSTRACT This essay Hill show the advantages of democracy in respect of authoritarian and totalitarian regimes, taking in account the point of view of the population involved. It will also argue that society must gain self-consciousness, even if it is gained only by a selected group of individuals. It will lastly argue that social systems opposed to pluralist democracy, such as harmonicist models, haven't shown to be flexible or able to adapt to changing human environments. KEY WORDS: Democracy, institutional theory, political elite, political apathy, common well.